engembangan E-Modul Sistem Koloid Berbasis Discovery Learning untuk SMA/MA - Ranny, Rahma (RC-INSTITUT, 2019)
Learning in the 2013 curriculum for all levels of education is using the scientific approach. One of learning model that is relevant to the application of the scientific approach is discovery learning. This research aims to determine the level of validity and practicality of e-module developed. The type of research conducted is Research and Development (R&D) and used 4-D model which includes four stages, define, design, develop, and disseminate. Validity and practicality of the colloidal system e-module based on discovery learning were tested. The validity test was carried out by two chemistry lecturers at FMIPA UNP and three chemistry teachers at SMAN 4 Pariaman using a validity questionnaire. Practicality test was carried out by three chemistry teachers and 21 students of class XI IPA 1 at SMAN 4 Pariaman using a practicality questionnaire. The average kappa moment (k) result of the validity and practicality tests by teacher and student of e-module are 0,89; 0,89; 0,79 with a very high validity category, very high practicality category from teacher and high practicality category from student. The data shows that the colloidal system e-module based on discovery learning for SMA/MA is valid and practical.